Effect of PbO on the elastics properties of borate and phosphate glass system - Kasim, Azman (2000)
The effect of PbO on the elastic properties phosphate of glass and borate glass system has been studied. A series of lead borate glasses [PbOx. (0.10 ≤ X ≤ 0.60)] were successfully synthesized. By using ultrasonic measurement system, the velocities of the propagated waves attained could be used to estimate the elastic properties of glass. In this studies, the velocities of propagated waves in lead borate and lead phosphate are found to decrease with the mole fraction of PbO. Meanwhile, the addition of PbO increases the density of g lasses. It shows that lead borate and lead phosphate glasses become more rigid but undergone a weakening structure. Hence, an addition of PbO will affect the elastic properties of glass. From the experimental results 'the elastic modulus C11 and C44, Young's modulus (E); bulk modulus (8) and Poisson ratio (0) are also found to vary with the mole fraction of PbO. The Oebye temperatures, which describe the thermal behaviour for isotropic materials such as glass also show a decreasing trend with the mole fraction of PbO. It seems that an addition of PbO into the borate and phosphate g lass systems changes the coordination of the glass structure and weakens the g lass network by the increase of non-bridging oxygens (N 80s). From the structural aspect, the lead borate glass consists of 803 and 804 units, which change markedly with the PbO content. At low PbO concentration (x ≤ 0.15), lead is assumed to assist in the formation of 804 tetrahedral. Whereas, for high PbO content (x> 0.15), some of lead act to form Pb04 pyramid. Meanwhile, for lead phosphate glasses , since the basic structure is Pb04 tetrahedral, hence an increment of PbO content tend to reduce the number of cross-linking P-O-P bonds between pairs of tetrahedral and increase the number of chains of P04 tetrahedral.